The Effect of Liquidity, Leverage, Institutional Ownership, and Sales Growth on Financial Distress on Property and Real Estate Companies Listed an The IDX 2016-2019 - Wiwit Octavia Nia Putri; Atwal Arifin (Majalah Ilmiah Bijak, 2021)
Financial distress is a financial condition where the company's finances are in an unhealthy or crisis condition. Financial distress which is quite disturbing the company's operational activities is a condition that must be immediately watched out and anticipated. This study aims to analyze the effect of liquidity, leverage, institutional ownership, and sales growth. The research was conducted on property and real estate companies listed on the IDX for the 2016-2019 period. Sampling in this study using purposive sampling technique, and obtained as many as 152 samples that match the criteria. Data analysis used multiple regression analysis. The results showed that the variables of liquidity, leverage, and institutional ownership have an effect on financial distress.